Seed germination performance of nine Arabica coffee (Coffea arabica L.) varieties under the laboratory condition after six months of storage period. - Ari Wibowo; Dwi Nugroho; Ucu Sumirat (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Coffee seeds are classified into intermediate seeds which require high moisture content during the storage and possess a short shelf life. Seed germination testing aims to determine the potential of a seed lot, evaluate seed quality during the storage and also to estimate the success of seedling in the nursery. This experiment aimed to determine the germination performance of several Arabica coffee varieties after being stored for six months at controlled temperature. Nine varieties of Arabica coffee, namely Abesinia-3, Andungsari-1, BLP, Gayo-2, Goiaba, Kartika-1, Kayumas, MP-3, and S-795 were used in this study. The seeds were harvested in the 2019 harvest season (September) and the germination was tested in April 2020. The germination test was carried out in laboratory by using petridish. The result showed that the tested Arabica coffee seeds still had a high germination percentage which was more than 85%. Only three varieties namely S-795, Abesinia-3, and Goiaba had low germination growth (<80%). Meanwhile, Kayumas, BLP, and Kartika-1 coffee varieties had the best germination growth with an average length of 34.19 mm; 39.79 mm and 39.41 mm, respectively. Kartika-1 variety needs 6–7 days to germinate; Kayumas, BLP, and Goiaba varieties took 7–8 days; S-795 and MP-3 took 10 days; as well as Andungsari-1, Abesinia-3, and Gayo-2 which took 10–12 days. Arabica coffee seeds that had a short germination time will had a high germination rate and otherwise. Each variety displayed a different germination performance. BLP, Kartika-1, Gayo-2 and MP-3 varieties had high potential germination, 86.67%; 89.17%; 86.67%, and 93.33%, respectively. Kayumas, BLP, and Kartika-1 varieties showed significantly longer germination, namely 34.19 mm; 39.79 mm and 39.41 mm, respectively. The fastest of average germination time was possessed by Kartika-1 variety (6.54 days) and the highest seed germination rate was also possessed by Kartika-1 variety (0.153 per day).